PEMBERDAYAAN MASYARAKAT LOKAL MELALUI PROGRAM EDUKASI SEJARAH DI MUSEUM LINGGARJATI KABUPATEN KUNINGAN - Muhammad Subhan; Hermansyah; Arik Darojat; Ungkeu Martin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Museums play a strategic role as a means of public education in enhancing community understanding of historical values while also supporting the preservation of cultural heritage. However, the low level of historical literacy among the public and the suboptimal utilization of museums as learning media have resulted in the educational potential of museums not being fully maximized. Therefore, this Community Service activity aims to improve public understanding of the history of the Linggarjati Agreement and to encourage community participation in preserving historical sites through a historical education program conducted at the Linggarjati Museum, Linggarjati Village, Cilimus District, Kuningan Regency. The method used in this activity is a participatory educational approach through historical outreach, interactive discussions, historical literacy, and educational visits to the museum. The evaluation of the activity was carried out using pretest and posttest methods involving 21 participants to measure the level of understanding before and after the educational program. The data obtained were then analyzed using the N-Gain test to determine the level of improvement in participants’ understanding. The results show that the average pretest score of 56.40 increased to 82.30 in the posttest. The N-Gain analysis result of 0.59 falls into the moderate category, indicating that the historical education program is sufficiently effective in improving public understanding and encouraging participation in the preservation of local cultural heritage.